Prevalence and determinants of home delivery among pregnant women in Somaliland: Insights from SLDHS 2020 data - Hodo Abdikarim; Abdisalam Hassan Muse; Mukhtar Abdi Hassan; Yahye Hassan Muse (Atención Primaria)
Objective: This cross-sectional study aimed to identify the determinants of home deliveries among women in Somaliland, with the objective of informing targeted interventions to improve maternal and child health outcomes. Design: A cross-sectional study design was employed, utilizing data from a nationally representative sample of 3250 women in Somaliland. A multivariate logistic regression analysis was conducted to examine the factors influencing the likelihood of home delivery. Site: The study was conducted in Somaliland, a region where home delivery remains prevalent. Participants: The study included 3250 women of reproductive age in Somaliland who had given birth. Interventions: No specific interventions were administered as part of this study. The focus was on understanding the factors associated with home deliveries. Main measurements: Sociodemographic, economic, and regional factors were examined as potential determinants of home deliveries. Education levels of women and their husbands, maternal age at first marriage and first birth, and household wealth were among the main measurements analyzed. Results: The analysis revealed that higher education levels were associated with a decreased likelihood of home delivery. Women with secondary (OR: 0.42, 95% CI: 0.32–0.55) or higher (OR: 0.21, 95% CI: 0.12–0.37) education were less likely to deliver at home than those with no education. Similarly, women whose husbands had a secondary (OR: 0.55, 95% CI: 0.41–0.73) or higher (OR: 0.43, 95% CI: 0.28–0.66) education were less likely to deliver at home. Increased maternal age at first marriage (OR: 1.04, 95% CI: 1.02–1.06) and first birth (OR: 1.03, 95% CI: 1.01–1.05) were significant predictors of home delivery. Lower household wealth was also associated with a higher likelihood of home delivery. Significant regional variations were observed, with certain regions showing higher rates of home deliveries compared to others. Conclusions: The findings highlight the importance of targeted interventions to address sociodemographic and regional disparities in the utilization of institutional delivery services in Somaliland. Strategies should focus on improving access to and quality of maternal healthcare services, empowering women's decision-making, and engaging men to address gender norms within households. Resumen: Objetivo: Este estudio transversal se propuso identificar los factores determinantes de los partos en el hogar entre las mujeres de Somalilandia, con el objetivo de informar de las intervenciones dirigidas a mejorar los resultados de salud materna e infantil. Diseño: Se empleó un diseño de estudio transversal, utilizando datos de una muestra nacional representativa de 3.250 mujeres en Somalilandia. Se realizó un análisis de regresión logística multivariante para examinar los factores que influyen en la probabilidad de dar a luz en casa. Emplazamiento: El estudio se llevó a cabo en Somalilandia, una región donde el parto en casa sigue siendo frecuente. Participantes: El estudio incluyó a 3.250 mujeres en edad reproductiva de Somalilandia que habían dado a luz. Intervenciones: No se administraron intervenciones específicas como parte de este estudio. La atención se centró en comprender los factores asociados a los partos domiciliarios. Mediciones principales: Se examinaron factores sociodemográficos, económicos y regionales como posibles determinantes de los partos en el hogar. Los niveles de educación de las mujeres y sus maridos, la edad materna en el momento del primer matrimonio y el primer parto y la riqueza del hogar fueron algunas de las principales medidas analizadas. Resultados: El análisis reveló que un mayor nivel educativo se asociaba con una menor probabilidad de parto en casa. Las mujeres con estudios secundarios (OR: 0,42; IC 95%: 0,32-0,55) o superiores (OR: 0,21; IC 95%: 0,12-0,37) tenían menos probabilidades de dar a luz en casa que las que no tenían estudios. Del mismo modo, las mujeres cuyos maridos tenían estudios secundarios (OR: 0,55; IC 95%: 0,41-0,73) o superiores (OR: 0,43; IC 95%: 0,28-0,66) tenían menos probabilidades de dar a luz en casa. Una mayor edad materna en el primer matrimonio (OR: 1,04; IC 95%: 1,02-1,06) y en el primer parto (OR: 1,03; IC 95%: 1,01-1,05) fueron predictores significativos de parto en casa. Una menor riqueza familiar también se asoció con una mayor probabilidad de parto en casa. Se observaron variaciones regionales significativas y algunas regiones mostraron tasas más elevadas de partos en casa que otras. Conclusiones: Los hallazgos destacan la importancia de las intervenciones específicas para abordar las disparidades sociodemográficas y regionales en la utilización de los servicios de parto institucional en Somalilandia. Las estrategias deben centrarse en mejorar el acceso y la calidad de los servicios de atención sanitaria materna, potenciar la toma de decisiones de las mujeres e implicar a los hombres para abordar las normas de género en los hogares.